Cartilage hair hypoplasia with cutaneous lymphomatoid granulomatosis. (10th May 2018) - Sathishkumar, D.; Gach, J. E.; Ogboli, M.; Desai, M.; Cole, T.; Högler, W.; Motwani, J.; Norton, A.; Morland, B.; Colmenero, I.
Summary: Cartilage–hair hypoplasia (CHH) is an autosomal recessive chondrodysplasia characterized by short‐stature, sparse hair and impaired cellular immunity. We describe a young girl who was diagnosed with CHH based on the findings of recurrent infections, short stature with metaphyseal chondrodysplasia, and a confirmed bi‐allelic RMRP gene mutation. At 13 years, the patient developed an Epstein–Barr virus (EBV)‐driven lymphoproliferative disorder involving the lung, which responded partially to chemotherapy. Simultaneously, she developed multiple indurated plaques involving her face, which had histological findings of granulomatous inflammation and EBV‐associated low‐grade lymphomatoid granulomatosis. The patient received a matched unrelated peripheral blood stem cell transplant at 15 years of age, and her immunological parameters and skin lesions improved. Lymphomatoid forms of granulomatosis and cutaneous EBV‐associated malignancies have not been described previously in CHH. This case highlights the possibility of EBV‐associated cutaneous malignancy in CHH.